Znaczenie motywacji w kaznodziejskiej posłudze słowa - Twardy, Jan (Śląskie Studia Historyczno-Teologiczne, 2011)
A good motivation is an important condition of fruitful proclaiming of God’s word – as listener to it should know why he should reach saintliness, choose virtue and avoid sin. Polish homilets of 19th century and the first half of 20th century paid attention to this problem writing about priest’s influence on the human will. This problem is still actual as the right motivation and reliable argumentation also determine worth of the sermon. The preacher should fully draw positive preternatural motives from Divine revelation which show that God loves us from the beginning and craves for our happiness (heaven). The response to God’s love should be the whole Chritian life. As people sin against God and deserve God’s punishment, there is also necessary the preternatural motivation in a negative aspect (hell). That is why the preacher should also praize the natural motivation – pointing at the fruits of virtuous life and the fatal effects of vices and sins. An abundant source of motivation is Bible and tradition of Church’s faith; helpful will also be examples drawn from hagiography, history and life experiences of people. So it is worth to study motivations of contemporary preaching to know its model and defy against errors that may be found as regards that matter.